The Slovene community in Italy and the Covid-19 pandemic - Brezigar, Sara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
Italy was the first country of the Western world to experience the outburst of the Covid-19 pandemic, and slowing it down required a swift and sizable adaptation of all aspects of life in Italy. Based on a preliminary qualitative study and relying on existing primary and secondary data sources, the author explores the effect of the Covid-19 pandemic on the Slovene community in Italy. Although the community shared the same fate as the rest of Italy's population in terms of restrictive measures and limitations to human rights, the author argues that some of the measures had a different, sometimes disproportionate and harmful effect on the community. Similarly, the changes in modus vivendi et operandi of the minority and its members that appeared as a side-effect of the pandemic may alter significantly the functioning of the minority in the future, and wider integration processes in the cross-border region may be slowed down or even reversed.
Keywords: integracija; Italija; izobraževanje; meja; narodne manjšine; pandemija covid 19; Slovenci v Italiji; Slovenija; slovenska manjšina; šolanje na daljavo